УПРАВЛІННЯ БРЕНДОМ ЗАКЛАДУ РЕСТОРАННОГО БІЗНЕСУ - Ostashevskyi, Oleg; Pavlova, Svitlana (Zhytomyr Ivan Franko State University, 2025)
The article explores the features of brand management in the restaurant business as a key tool for enhancing the enterprise’s competitiveness and ensuring its stable development in a dynamic market environment. The relevance of the topic is due to the growing role of brand as an element of intangible assets that affects customer perception of service quality, trust in the enterprise, loyalty formation among the target audience, and building an emotional connection with the consumer. The article analyzes scientific approaches to understanding brand and brand management, reveals the key elements of effective restaurant brand management, including brand strategy, visual identity, emotional image, brand communications, and the role of staff in maintaining brand standards. Particular attention is paid to the specifics of branding in the restaurant business, especially the high emotionality of the service, the influence of the physical environment, the role of customer experience, interaction through social networks, and reputation risks in the online space. The article highlights the main stages of brand management – from market research to brand implementation and effectiveness monitoring. It also analyzes modern tools for brand promotion, such as content marketing, influencer marketing, interactive events, and brand storytelling. Based on the analysis, conclusions are drawn regarding the importance of an integrated approach to restaurant brand management, combining strategic thinking, creative vision, and adaptability to changes in consumer behavior. The findings can be useful for owners, marketers, brand managers, and restaurant executives who strive to build a strong, recognizable, and emotionally appealing brand that ensures long-term customer loyalty and a stable market position.